2016
DOI: 10.1152/ajpregu.00032.2016
|View full text |Cite
|
Sign up to set email alerts
|

CLOCK regulates mammary epithelial cell growth and differentiation

Abstract: Circadian clocks influence virtually all physiological processes, including lactation. Here, we investigate the role of the CLOCK gene in regulation of mammary epithelial cell growth and differentiation. Comparison of mammary morphology in late-pregnant wild-type and ClockΔ19 mice, showed that gland development was negatively impacted by genetic loss of a functional timing system. To understand whether these effects were due, in part, to loss of CLOCK function in the gland, the mouse mammary epithelial cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…A short-day photoperiod during the nonlactating dry period increased expression of genes that regulate proliferation and differentiation of cells in the mammary gland (Bentley et al, 2015); it also attenuated rhythms of expression of core clock genes in mammary tissue of goats (Casey et al, 2018). Our work in cells and rodents supports a role for the circadian clocks in regulation of mammary epithelial growth and differentiation (Casey et al, 2016). Thus, it is possible that attenuation of circadian rhythms in the PS treatment affected mammary-specific clocks in a manner that increased proliferation of the mammary tissue preparturition and is reflected as an increase in milk yield during lactation.…”
Section: Circadian Disruption During Preparturition Increased Milk Ansupporting
confidence: 61%
See 1 more Smart Citation
“…A short-day photoperiod during the nonlactating dry period increased expression of genes that regulate proliferation and differentiation of cells in the mammary gland (Bentley et al, 2015); it also attenuated rhythms of expression of core clock genes in mammary tissue of goats (Casey et al, 2018). Our work in cells and rodents supports a role for the circadian clocks in regulation of mammary epithelial growth and differentiation (Casey et al, 2016). Thus, it is possible that attenuation of circadian rhythms in the PS treatment affected mammary-specific clocks in a manner that increased proliferation of the mammary tissue preparturition and is reflected as an increase in milk yield during lactation.…”
Section: Circadian Disruption During Preparturition Increased Milk Ansupporting
confidence: 61%
“…Human and rodent studies support a mechanistic link between circadian disruption and the development of metabolic diseases (Pillar and Shehadeh, 2008;Gangwisch, 2009;Möller-Levet et al, 2013). Of particular interest is that metabolism is altered and lactation performance is impaired in mice with mutations in the CLOCK gene, one of the genes that make up the core molecular clocks that generate circadian rhythms of gene expression (Dolatshad et al, 2006;Hoshino et al, 2006;Casey et al, 2016). Here our aim was to determine whether the circadian timing system plays a role in maintaining homeostasis and regulating the onset of lactation in transition dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment with high-serum concentrations induces robust circadian rhythms in the cultured cells (28,29). In addition, this treatment also affects cell-cycle synchronization (30). In this study, Wee1 expression did not show circadian rhythm between 24 and 48 hours after serum treatment, and we confirmed that Clock genes directly affect xCT levels without cell-cycle effects in serum-shocked colon 26 cells.…”
Section: Sulfasalazine Dosing Time Affects Combination Therapysupporting
confidence: 73%
“…29 The circadian clock has been implicated in gating control of the cell cycle at a number of targets: induction of Wee1 for inhibition of Cyclin B1 at the G 2 /M (Gap 2 /Mitosis) transition, 30 induction of p20 and p21 at the G 1 /S (Gap 1 /Synthesis) transition, 31,32 and regulation of p27, Cyclin D1, and c-Myc for progression through G 1 . [33][34][35][36] Cell turnover rate is very low in the parathyroid gland under normal conditions; with an estimated mean life span of normal parathyroid cells being 19 years in humans and 2 years in rats. 37 This rate increases dramatically in secondary hyperparathyroidism (sHPT) caused by chronic kidney disease (CKD).…”
mentioning
confidence: 99%